2021
DOI: 10.1093/crocol/otab054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Factors for Coexisting Sinusitis and Inflammatory Bowel Disease

Abstract: BACKGROUND This study aimed to analyze the association of coexisting sinusitis and IBD, establish significant factors involved in their development, and enable further biological correlation between these two diseases. METHODS The IBD and Sinusitis Study at __________ (TISSUe) is a retrospective, single-center study. We reviewed patients to confirm IBD and chronic sinusitis diagnoses. Case-control propensity score matching wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Several studies have explored the link between CRS and IBD previously. A small single-center retrospective study from UChicago Medicine suggested that the diagnosis and duration of UC may be more associated with development of CRS, while CRS may be considered as an extraintestinal manifestation of IBD due to CRS precedes IBD in some patients [14] . Besides, Lin et al found that patients with IBD history, especially UC, had an increased risk of subsequent development of CRS [16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored the link between CRS and IBD previously. A small single-center retrospective study from UChicago Medicine suggested that the diagnosis and duration of UC may be more associated with development of CRS, while CRS may be considered as an extraintestinal manifestation of IBD due to CRS precedes IBD in some patients [14] . Besides, Lin et al found that patients with IBD history, especially UC, had an increased risk of subsequent development of CRS [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is worthy of further studying the relationship between CRS and IBD. Actually, there are several studies having already evaluated the relationship between CRS and IBD [14][15][16][17] , but the results are inconsistent. However, it is noteworthy that these evidence come only from observational studies, which are hard to infer causality and avoid the impact of confounding factors [18] .…”
Section: Introductionmentioning
confidence: 99%
“…In real-world studies, patients with IBD often showed more nasal and sinus symptoms than the control group [ 12 , 17 , 18 ]. However, some large-scale, retrospective studies showed that there was no significant evidence for the association between IBD and the subsequent development of CRS [ 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study, we found an increased risk of subsequent UC development in patients with CRSsNP, but not in patients with CRSwNP. Additionally, another recent study investigating the bidirectional development between sinusitis and IBD reported that the duration of IBD, UC, steroid exposure, and younger age of IBD diagnosis were associated with subsequent sinusitis in patients with UC, whereas steroid exposure and duration of sinusitis were significantly associated with subsequent IBD in patients with sinusitis [ 25 ]. For these reasons, we hypothesize that UC and CRSsNP have been intrinsically associated with a network of deregulated inflammatory mediators, such as the interleukin (IL)-33/ST2 pathway [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%